Respuesta :
The answer is: [A]: (x + 2) (x² − 2x + 4).
_______________________________
Explanation:
_____________________________
Note the formula:
___________________
a³ + b³ = (a + b) (a² − ab + b²)
_________________________________
x³ + 8 can be written as x³ + 2³ ; since 2³ = 8
______________________________
So, using the formula:
_____________________
a³ + b³ = (a + b) (a² − ab + b²) ;
______________________________
x³ + 8 ; or, x³ + 2³ ; can be factored; where a = x and b = 2.
__________________________________
→ Substitute these values for "a" and "b"; and rewrite:
__________________________________
→ x³ + 2³ = (x + 2) (x² - x*2 + 2²) ;
__________________________________
→ Simplify, and rewrite as:
__________________________________
→x³ + 8 = x³ + 2³ = (x + 2) (x² − 2x + 4) ;
__________________________________
→which is our first answer choice, "[A]".
_________________________________________
_______________________________
Explanation:
_____________________________
Note the formula:
___________________
a³ + b³ = (a + b) (a² − ab + b²)
_________________________________
x³ + 8 can be written as x³ + 2³ ; since 2³ = 8
______________________________
So, using the formula:
_____________________
a³ + b³ = (a + b) (a² − ab + b²) ;
______________________________
x³ + 8 ; or, x³ + 2³ ; can be factored; where a = x and b = 2.
__________________________________
→ Substitute these values for "a" and "b"; and rewrite:
__________________________________
→ x³ + 2³ = (x + 2) (x² - x*2 + 2²) ;
__________________________________
→ Simplify, and rewrite as:
__________________________________
→x³ + 8 = x³ + 2³ = (x + 2) (x² − 2x + 4) ;
__________________________________
→which is our first answer choice, "[A]".
_________________________________________
Answer:
A
Step-by-step explanation:
other guy said it and I got it right.